DAMPAK AKUISISI TERHADAP KINERJA PT BANK MNC INTERNASIONAL TBK, (MNC BANK) - Sumarni, Yuyun Yuyun (EKONOMIA, 2018)
Competition in the business world becomes more intense, which requires every company to always develop the corporate strategies in order to survive or even more berkembang.Untuk that companies need to develop an appropriate strategy in order Ordinary maintain its existence and improve their performance. One of them is to make acquisitions.               This study aims to determine the bank's financial performance before and after the acquisition of PT MNC Bank International, Tbk (MNC Bank). As a measure of financial performance of the bank used the bank's financial ratios. Financial ratio used in this study is Return On Equity (ROE), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL). The data used are the Balance Sheet, Statement of Comprehensive Income and Assets Quality, Calculation Reports Minimum Capital Requirement (CAR). This study is to compare, so it requires different test to the bank's financial performance before and after the acquisitions using Paired Sample T-test.               The results of this study indicate the financial performance of PT Bank MNC International, Tbk (MNC Bank) changes subsequent to the different test and it can be seen that the financial ratio that shows the significant difference between before and after the acquisition of ROE and LDR is decreased, otherwise better prior to the acquisition of CAR and NPL increased better expressed after the acquisition.